Development of chickpea wilt (Fusarium oxysporum f. sp. ciceri) incidence in relation to soil edaphic and aerial environments - SINGH, R K; SILAVAT, SUNIL; PATIDAR, JAGDISH KUMAR; KASHYAP, VIVEK (The Indian Journal of Agricultural Sciences, 2019)
Correlation between incidence of chickpea wilt [Fusarium oxysporum f. sp. ciceri (Padwick) Matua & K Sato (foc)] and soil edaphic factors on four lines, viz. JG 315, IGP 187, IGP 29 and JG 62 was studied. There was a significant correlation between disease incidence and soil temperature and moisture (%). The test entries showed positive correlation with soil temperature and negative correlation with soil moisture as well as contributed 54.7% (JG 315), 56.32%, (IGP 187), 54.88% (IGP 29) and 39.42% (JG 62) in development of wilt. Three different levels of temperatures, viz. 20, 27 and 34, two different levels of relative humidity, viz. 60, 80% and two inoculum load (5 and 10%) exhibited positive correlation with wilt incidence. Statistically, aerial temperature (0.7226**) and inoculum load (0.6435**) showed significant positive correlation with wilt incidence, while relative humidity (0.1315) was found to be non-significant.